Faktor-Faktor Yang Mempengaruhi Animo Masyarakat Untuk Melakukan Vaksin Covid-19 Di Kelurahan Tempe: Factors Affecting Public Enthusiasm to Get the COVID-19 Vaccine in Tempe Village - Arafah, Eka Hardianti; Hasan, Masrah; Arismunandar, Salmudi; Yammar, Yammar; Fatmawati, Fatmawati; Ikdafila, Ikdafila (Innovative: Journal Of Social Science Research, 2025)
The success of the COVID-19 vaccination program ultimately depends on high vaccine uptake. This study aims to determine the Factors Affecting Public Enthusiasm to Get the COVID-19 Vaccine in Tempe Village. The type of research is Cross Sectional by measuring the research variables at one time. Data was collected using a questionnaire. The research sample was determined using the Slovin formula totaling 370 samples, namely respondents who had received the 1st and 2nd doses of the COVID-19 vaccine. The independent variables in this study are Government Policy, Public Knowledge, Public Awareness while the dependent variable is Public Enthusiasm. The results of the Chi-Square test, namely the Government Policy variable obtained a value (P = 0.000), the Public Knowledge variable (P = 0.004), and the Public Awareness variable (P = 0.000) meaning that the three variables obtained the result α <0.05. Based on this analysis, it is concluded that these three factors have a Relationship to Public Enthusiasm to Get the COVID-19 Vaccine in Tempe Village.